Randomised controlled trial of paracetamol or ibuprofen, as required for fever and pain in the first year of life, for prevention of asthma at age 6 years: paracetamol or ibuprofen in the primary prevention of asthma in Tamariki (PIPPA Tamariki) protocol. Issue 12 (10th December 2020) - Tan, Eunicia; Braithwaite, Irene; McKinlay, Christopher; Riley, Judith; Hoare, Karen; Okesene-Gafa, Karaponi; Semprini, Alex; Sheridan, Nicolette; Grant, Cameron; Johnson, David; Weatherall, Mark; Asher, Innes; et al.
Abstract : Introduction: Asthma is one of the most common diseases in the world and is a global public health burden. There is an urgent need for research that leads to evidenced-based primary prevention strategies to reduce the prevalence of asthma. One novel risk factor that might have a role in the pathogenesis of asthma is the use of paracetamol in early life. This trial aims to determine if paracetamol, compared with ibuprofen use, as required for fever and pain in the first year of life, increases the risk of asthma at age 6 years. Methods and analysis: The Paracetamol and Ibuprofen in Primary Prevention of Asthma in Tamariki trial is a multicentre, open-label, two-arm parallel randomised controlled trial. 3922 infants born at ≥32 weeks' gestation will be randomly allocated to receive only paracetamol or only ibuprofen for treatment of fever and pain, if required in the first year of life. The primary outcome is asthma at 6 years of age, defined as the presence of wheeze in the preceding 12 months. Secondary outcomes include hospital admissions for bronchiolitis, wheeze or asthma in the first year of life, and within the first 6 years of life; wheeze at 3 years of age; eczema within the first year and at 3 and 6 years of age; atopy at 3 and 6 years of age. Ethics and dissemination: The trial has been approved by the Northern A Health and Disability Ethics Committee of New Zealand (17/NTA/233). Dissemination plans include publication in international peer-reviewed journals, and presentation at national and international scientific meetings, assimilation into national and international guidelines, and presentation of findings to lay audiences through established media links. Trial registration number: ACTRN12618000303246; Pre-results.